The therapeutic alliance in blended versus face-to-face cognitive behavioral therapy for adolescents and young adults with a depressive disorder - Miriam L.F.M. van Seters; Sanne P.A. Rasing; Mireille J. Huvenaars; Ad Vermulst; Denise H.M. Bodden; Yvonne A.J. Stikkelbroek (Internet Interventions)
Introduction: A depressive disorder during adolescence is a serious and disabling disorder, which has a high impact on the development of adolescents. Blended treatment, combining online and face-to-face sessions, is effective and can reduce some of the barriers for adolescents to use mental health care. There is a lack of knowledge about whether therapeutic alliance is established in blended treatment for adolescents and young adults suffering from a depressive disorder. This study examines whether the quality of the therapeutic alliance differs when cognitive behavior therapy (CBT) is delivered in combination with online intervention (b-CBT) compared to solely face-to-face (FtF-CBT) and the extent to which a stronger therapeutic alliance is associated with better treatment outcome. Methods: A pragmatic quasi-experimental design was used. Data collected within two separate studies were combined. A total of 85 participants (80 % female), aged 13–22 (mean = 16.63, SD = 1.92) were recruited within mental health care institutions and diagnosed with a depressive disorder (using K-SADS). Assessments were done at pre-treatment (T0), after five weeks (T1), after ten weeks (T2), post-treatment (T3) and one to four weeks after treatment (T4) and included measures of depressive symptomatology (CDI-2). The therapeutic alliance was measured at T1, T2 and T3 by the TASC. t-tests for independent samples were used to test differences in therapeutic alliance rates between b-CBT and FtF-CBT at post-treatment. A linear growth model for depressive symptoms based on five time points with Latent Growth Curve Analysis (LGCA) was used to test whether the therapeutic alliance is associated with depressive symptoms. Results: No differences in therapeutic alliance between b-CBT and FtF-CBT were found on either client-rated or therapist-rated therapeutic alliance. For both intervention groups, no significant association between the therapeutic alliance and depressive outcome was found. Discussion: This study shows that providing part of CBT using an online environment does not have a negative impact on the therapeutic alliance. In contrast to earlier research, no association was found between the therapeutic alliance and therapy outcome in neither the b-CBT nor the FtF-CBT intervention.